2005
DOI: 10.1038/sj.bjc.6602773
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial apoptotic activity of angiocidin is dependent on its polyubiquitin binding activity

Abstract: We recently cloned the full-length cDNA of a tumour-associated protein. The recombinant protein expressed in bacteria and referred to as angiocidin has potent antitumour activity in vivo and in vitro. Angiocidin inhibits tumour growth and angiogenesis by inducing apoptosis in endothelial cells. Based on the sequence similarity of angiocidin to S5a, one of the major polyubiquitin recognition proteins in eukaryotic cells, we postulated that the antiendothelial activity of angiocidin could be due in part to its p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 17 publications
(28 reference statements)
0
7
0
Order By: Relevance
“…However, emerging evidence has implicated a potential role of CYLD. A report of polyubiquitin as a discriminatory marker for synthetic versus contractile VSMCs, along with a subsequent finding that angiocidin is regulated by polyubiquitination, has raised the possibility that CYLD is intimately involved in the vascular lesion process, thus revealing a potential therapeutic target [42,52]. Indeed, CYLD is upregulated in injured carotid arteries of rats, reduces cyclin D1 levels, and is capable of suppressing vascular lesion formation.…”
Section: Cyld and The Cardiovascular System: A New Frontiermentioning
confidence: 99%
“…However, emerging evidence has implicated a potential role of CYLD. A report of polyubiquitin as a discriminatory marker for synthetic versus contractile VSMCs, along with a subsequent finding that angiocidin is regulated by polyubiquitination, has raised the possibility that CYLD is intimately involved in the vascular lesion process, thus revealing a potential therapeutic target [42,52]. Indeed, CYLD is upregulated in injured carotid arteries of rats, reduces cyclin D1 levels, and is capable of suppressing vascular lesion formation.…”
Section: Cyld and The Cardiovascular System: A New Frontiermentioning
confidence: 99%
“…We previously reported that tTgase present in HUVE cell extracts bound to recombinant angiocidin immobilized on Sepharose beads (Dimitrov et al, 2005). The peptide eluted from the angiocidin-Sepharose beads was identified by mass spectral analysis of its tryptic peptides.…”
Section: Resultsmentioning
confidence: 99%
“…While investigating the interaction of angiocidin with potential HUVE cell protein binding partners using angiocidin-affinity chromatography (Dimitrov et al, 2005), we discovered that one of the protein bands that was eluted from the column was a 150 kDa protein whose tryptic fragments matched those of tissue transglutaminase 2 (tTgase) as revealed by mass spectral fingerprinting. In this study we have attempted to investigate the significance of this finding as it relates to the anti-tumor activity of recombinant angiocidin.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations